Ecological impacts of photosynthetic light harvesting in changing aquatic environments: A systematic literature map. Issue 3 (22nd March 2022) - Hintz, Nils Hendrik; Schulze, Brian; Wacker, Alexander; Striebel, Maren
Abstract: Underwater light is spatially as well as temporally variable and directly affects phytoplankton growth and competition. Here we systematically (following the guidelines of PRISMA‐EcoEvo) searched and screened the published literature resulting in 640 individual articles. We mapped the conducted research for the objectives of (1) phytoplankton fundamental responses to light, (2) effects of light on the competition between phytoplankton species, and (3) effects of climate‐change‐induced changes in the light availability in aquatic ecosystems. Among the fundamental responses of phytoplankton to light, the effects of light intensity (quantity, as measure of total photon or energy flux) were investigated in most identified studies. The effects of the light spectrum (quality) that via species‐specific light absorbance result in direct consequences on species competition emerged more recently. Complexity in competition arises due to variability and fluctuations in light which effects are sparsely investigated on community level. Predictions regarding future climate change scenarios included changes in in stratification and mixing, lake and coastal ocean darkening, UV radiation, ice melting as well as light pollution which affect the underwater light‐climate. Generalization of consequences is difficult due to a high variability, interactions of consequences as well as a lack in sustained timeseries and holistic approaches. Nevertheless, our systematic literature map, and the identified articles within, provide a comprehensive overview and shall guide prospective research. Abstract : Underwater light is spatially and temporally variable in its intensity (quantity) and spectrum (quality) with species‐specific consequences for phytoplankton. Climate change further affects the light availability in aquatic ecosystems and consequently phytoplankton ecology. Here, we systematically mapped previously published literature to provide an extensive overview of trends and gaps in research, covering the effects of light on phytoplankton.